Oral versus intravenous omeprazole in management of bleeding peptic ulcer: a randomized controlled trial - Ahmed S Abdelmohsen; Zeinab N Ahmed; Ahmad F. Hasanain; Mohamed A.A. Abozaid; Waleed A Hassan (Wolters Kluwer Medknow Publications, 2023)
Background Upper gastrointestinal bleeding (UGIB) is a common gastrointestinal emergency with significant morbidity and mortality. Intravenous (IV) route administration of proton pump inhibitors is more commonly used for prevention of bleeding; however, it is more expensive and invasive than the oral route. We, herein, compared between oral and IV omeprazole in patients with high-risk UGIB regarding outcome. Patients and methods Patients with high risk for rebleeding peptic ulcers were included. All patients initially received IV omeprazole, and then esophagogastroduodenoscopy with hemostatic procedure was done. Thereafter, the patients were allocated to group A, who received oral omeprazole, and group B, who received IV omeprazole. The patients were followed up for 2 weeks for signs of rebleeding. Reendoscopy, angioembolization, or surgery was provided when needed (NCT04170270). Results The study included 189 patients (96 in group A and 93 in group B). Frequency of rebleeding was higher among patients in group B (40%) compared with those in group A (30%) (P: 0.1). Reendoscopy was more frequently required for patients in group B (16.1%) than those in group A (3.1%) (P<0.001). Surgery was mandatory for three (3.2%) patients in group B, whereas angioembolization was used nearly equally in both groups (31.3% in group A vs. 29% in group B). Admission to ICU was more frequently needed (P: 0.02) and the length of hospital stays was longer (P: 0.003) for patients of group B. Regarding UGIB-related deaths, three (3.1%) patients from each group died. Conclusion Oral omeprazole is not inferior to IV omeprazole as adjuvant therapy to control peptic ulcer bleeding and to reduce the frequency of rebleeding.